Controlled Natural Language Workshop on Controlled Natural Language, CNL 2009, Marettimo Island, Italy, June 8-10, 2009. Revised Papers - Fuchs, Norbert E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-workshop proceedings of the Workshop on Controlled Natural Language, CNL 2009, held in Marettimo Island, Italy, in June 2009. The 16 revised full papers presented together with 1 invited lecture were carefully reviewed and selected during two rounds of reviewing and improvement from 31 initial submissions. The papers are roughly divided into the two groups language aspects and tools and applications. Note that some papers fall actually into both groups: using a controlled natural language in an application domain often requires domain-specific language features.
Language Aspects -- An Evaluation Framework for Controlled Natural Languages -- Rhetorical Compositions for Controlled Natural Languages -- Anaphora Resolution Involving Interactive Knowledge Acquisition -- Talking Rabbit: A User Evaluation of Sentence Production -- Naturalness vs. Predictability: A Key Debate in Controlled Languages -- Implementing Controlled Languages in GF -- Polysemy in Controlled Natural Language Texts -- Economical Discourse Representation Theory -- Controlled English Ontology-Based Data Access -- SBVR$1 (Bs Approach to Controlled Natural Language -- Tools and Applications -- The Naproche Project Controlled Natural Language Proof Checking of Mathematical Texts -- On Designing Controlled Natural Languages for Semantic Annotation -- Development of a Controlled Natural Language Interface for Semantic MediaWiki -- A Controlled Language for the Specification of Contracts -- Rabbit to OWL: Ontology Authoring with a CNL-Based Tool -- Writing Clinical Practice Guidelines in Controlled Natural Language -- What Are Controlled Natural Languages? -- On Controlled Natural Languages: Properties and Prospects.s
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Information Systems Applications (incl.Internet).; Mathematical Logic and Formal Languages; Database Management; Data Mining and Knowledge Discovery